Improved efficacy of ramucirumab plus docetaxel after nivolumab failure in previously treated non‐small cell lung cancer patients. Issue 4 (27th February 2019) - Shiono, Ayako; Kaira, Kyoichi; Mouri, Atsuto; Yamaguchi, Ou; Hashimoto, Kosuke; Uchida, Takahiro; Miura, Yu; Nishihara, Fuyumi; Murayama, Yoshitake; Kobayashi, Kunihiko; Kagamu, Hiroshi
Abstract : Background: It is unclear whether the chemotherapy response improves after exposure to immunotherapy. Antiangiogenic agents have been shown to stimulate the immune system and cause synergistic effects that stimulate tumor shrinkage. We conducted a retrospective study to evaluate improvement of the efficacy of ramucirumab plus docetaxel after the failure of nivolumab as a PD‐1 inhibitor. Methods: From February 2016 to December 2017, 152 patients with non‐small cell lung cancer (NSCLC) administered nivolumab in our institution were identified. We reviewed the records of 20 NSCLC patients administered ramucirumab plus docetaxel after nivolumab failure. The overall response rate (ORR), progression‐free survival (PFS), and overall survival (OS) were investigated. Pegylated granulocyte colony‐stimulating factor was prophylactically administered to 18 patients (90%) after the administration of ramucirumab plus docetaxel. Results: The median age of the patients was 70 (range: 55–77) years. Twelve patients were male and eight were female. The histology was adenocarcinoma in 16 patients, squamous cell carcinoma in three, and other in one. The ORR of ramucirumab plus docetaxel was 60%, and the PFS and OS were 169 and 343 days, respectively. Among the 20 patients, 12 achieved a partial response, giving an ORR of 60.0%. Six patients had stable disease and two had progressive disease. The disease control rate was 90%. Gastrointestinal adverse events were frequently observed in 19 patients. Conclusions: Ramucirumab plus docetaxel achieved a higher response rate when administered immediately after nivolumab failure compared to regimens without prior nivolumab administration.